A comicidade nas crônicas de Millôr Fernandes: o cômico além do riso - Oliveira, Erinaldo Ferreira de (2017)
The comic goes through changes from the antiquity to the present day, with various functions in society, whether with the form of seeking pleasure, or with social integration or even the social correction. The comic must be understood not only the pleasure of laughter, but also in it can be linked new information, the denunciation and even contribute to the formation of the more critical citizen. This research aims to investigate comedy in the chronicles of Millôr Fernandes, the role played by the comic in the corpus under analysis and the lines between laughter. We seek to study the comic forms described by the theorists Bergson (1983) and Freud (1905), and give a different view of what is mediated and what most people think about comedy. The texts that we will use to the chronic genre, which has the characteristic of being short stories, published in newspapers and magazines, and most of them bring indirect criticism to something or something.